Distance Learning Assessment (DLA) Elementary School During the Covid-19 Pandemic - Taufiq Satria Mukti; Sandy Tegariyani Putri Santoso; Wiku Aji Sugiri (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
The Covid-19 pandemic has had a significant impact on the implementation of learning. Research that explores the implementation of distance learning assessments during the pandemic is carried out using a mix-method approach. This approach is used to explore quantitative and qualitative information in depth. Quantitative data were obtained by surveying the teachers of SD N 2 Ngijo and SD Integrative Islamic Pesantren Rakyat. Qualitative data were obtained by field study and interviews with school administrators (principals and teachers) and parents of students. The results showed that based on the aspects of Online Assessment Implementation, Assessment Principles, and Reliability of the assessment instruments used in distance learning assessments, the score was more than 60%. This percentage is in the excellent category for the implementation of distance learning assessment. However, in reality, many factors have a significant influence on the implementation of distance learning assessments. Economic factors are the main factors in providing supporting facilities and infrastructure in carrying out distance learning assessments that do not take place according to concepts and theories.